Evidence-based medicine in neuropathic pain: a systematic review, meta-analysis, sequential analysis and network meta-analysis of randomised controlled trials - Alharbi, Ghaleb (2018)
Background Many randomised controlled trials (RCTs) are available to support using different pharmacotherapy agents in the management of various neuropathic pain conditions. However, choosing these pharmacotherapy agents for neuropathic pain is challenging, due to the limited evidence-based knowledge to support the use of different pharmacotherapy agents in different neuropathic pain conditions. Aims The aim of this PhD is to evaluate the efficacy and safety of oral and topical pharmacotherapies for managing neuropathic pain by deriving placebo and active comparative efficacy and safety evidence from RCTs. Methods This research used three approaches to summarise and synthesise evidence from randomised controlled studies including: a systematic review of placebo and active control RCTs to summarise and criticise the current evidence in neuropathic pain; a meta-analysis and sequential analysis of eligible studies to provide a more precise estimate of the overall treatment effects; and a network meta-analysis to estimate the relative effectiveness of the most commonly used interventions in neuropathic pain. Results Systematic review Two hundred placebo and active-controlled trials met the inclusion criteria. A wide range of different treatments were studied in these trials, including anticonvulsants, antidepressants, opioids and topical capsaicin and lidocaine.Most of the included studies were parallel placebo-controlled trials and commonly lasted for 3 to 12 weeks. In addition, the vast majority of the included RCTs were conducted in participants with painful diabetic neuropathy and post-herpetic neuralgia, while only a few trials were conducted in participants with central neuropathic pain conditions. Pairwise meta-analysis Sixty seven trials were eligible for the pairwise meta analysis of efficacy outcomes. Of the anticonvulsants group pregabalin and gabapentin compared with placebo demonstrated efficacy for 50% and 30% pain reduction and global improvement in patients with neuropathic pain. The efficacy of anticonvulsants varied in different types of neuropathic pain. Gabapentin when compared against a placebo was better than a placebo in PHN and PDN, while pregabalin was significantly effective in patients with post-herpetic neuralgia (PHN) and painful diabetic neuropathy (PDN) but not in patients with HIV associated neuropathic pain. Others anticonvulsant agents, such as lamotrigine, valproic acid, topiramate, levetiracetam and oxcarbazepine, were tested in a small number of trials. These did not provide useful benefits compared with a placebo for a 50% and 30% pain reduction. Of the antidepressant group, duloxetine when compared to a placebo demonstrated efficacy for 50% and 30% pain reduction in diabetic neuropathic pain. A few active comparison trials failed to demonstrate superior efficacy of one drug over another for a 50% and 30% reduction in neuropathic pain. Trial sequential analysis To examine the reliability and conclusiveness of the available evidence, trialsequential analysis has been applied in this study. The results show convincing evidence of the efficacy of some interventions (e.g. pregabalin, gabapentin and duloxetine) to reduce pain by 50% in some neuropathic pain conditions (e.g. diabetic neuropathic pain and post-herpetic neuralgia). The continuation of RCTs of pregabalin and duloxetine in diabetic neuropathy and gabapentin in post-herpetic neuralgia is not necessary as there appears to be sufficient evidence of the efficacy of these treatments in the management diabetic neuropathic pain and post herpetic neuralgia. Further RCTs of duloxetine, pregabalin and gabapentin are however required for central neuropathic pain. In contrast, the analysis failed to provide evidence that opioids and high concentration capsaicin demonstrate a 50% pain reduction. Network meta-analysis Twenty-eight trials were eligible for the network meta-analysis. The results incorporating both direct-comparison and indirect-comparison evidence suggested that there is no superiority of duloxetine over amitriptyline, pregabalin and gabapentin in achieving at least a 30% and 50% pain reduction with a treatment duration of 7 to 12 weeks in patients with neuropathic pain conditions, such as diabetic neuropathic pain, postherpetic neuralgia and spinal cord injury. Conclusions In summary, this research has found that some good quality trials provide good evidence regarding the efficacy of duloxetine, pregabalin and gabapentin in a minority of patients with neuropathic pain. Until advancements in developing mechanism-based approaches and improved clinical trial design become available, the routine use of these medications is unlikely to be changed. This may support the hypothesis that traditional RCTs might not be a suitable method of choice to address provisional health questions in routine clinical practice.